2020
DOI: 10.1093/cid/ciaa527
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Alcohol Use Are Associated With Latent Tuberculosis Infection in Adults Living With Human Immunodeficiency Virus

Abstract: We assessed associations between hazardous alcohol use and latent tuberculosis infection (LTBI) among adults living with HIV in Uganda. We compared tuberculin skin test positivity across medium, high, and very-high alcohol use levels, classified by AUDIT-C scores. In multivariable analysis, very-high use was associated with LTBI (aOR 1.61, 95%CI:1.03-2.50).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…to increase the likelihood of LTBI (41) and TB,(42) which supports our findings. The cause could be multifactorial.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…to increase the likelihood of LTBI (41) and TB,(42) which supports our findings. The cause could be multifactorial.…”
Section: Discussionsupporting
confidence: 89%
“…(39,40) Additionally, ART is implicated in various components of metabolic syndrome, including an increased risk of hyperglycaemia and diabetes. [41] However, our study only assessed selfreported diabetes and did not measure the haemoglobin A1c (HbA1c) level to determine its association with LTBI. We hypothesised that being on ART for >3 years resulted in CD4 recovery to at least the lower end of the normal range with increased yield from IGRA testing.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of LTBI in this study was found to be as high as 65%. Among persons living with HIV in western Uganda who are engaged in hazardous alcohol use, the prevalence of LTBI based on TST positivity was reported at 35% [ 18 ]. In this study, the prevalence of LTBI among women was 33.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of both latent TB infection (LTBI) and active TB disease is higher among persons with alcohol use disorders (AUD) than those without AUD ( 17 ). For example, one study in New York City found a 28-fold higher rate of active TB disease among those with AUD as compared to age-matched individuals without AUD ( 18 ).…”
Section: Alcohol and Tb Epidemiologymentioning
confidence: 99%